2003
DOI: 10.1046/j.1439-0418.2003.00727.x
|View full text |Cite
|
Sign up to set email alerts
|

Cultured mosquito cells Aedes albopictus C6/36 (Dip., Culicidae) responsive to 20‐hydroxyecdysone and non‐steroidal ecdysone agonist

Abstract: A cell line derived from an important mosquito, Aedes albopictus Skuse, was responsive to treatments with the insect moulting hormone 20-hydroxyecdysone (20E) and two new insecticides, RH-5849 and RH-5992, by cell clumping and inhibition of cell proliferation. The Aedes C6/36 cells showed typical numerous long extensions, and fluorescent BODIPY Ò -phalloidin staining demonstrated that they resulted from F-actin polymerization. In addition, the ultrastructure of treated cells showed a high degree of vacuolariza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 32 publications
2
8
0
Order By: Relevance
“…5.3d). The appearance of long slender neurite-like extensions may reflect a general stress response, rather than a specific effect of the heavy metals as this particular morphology was also obtained when cells were treated with 20-OH ecydosone (Smagghe et al 2003) and the F-actin poison cytochalasin B (Fig. 5.3e).…”
Section: Generalcellmorphology(lightmicroscopy)mentioning
confidence: 83%
“…5.3d). The appearance of long slender neurite-like extensions may reflect a general stress response, rather than a specific effect of the heavy metals as this particular morphology was also obtained when cells were treated with 20-OH ecydosone (Smagghe et al 2003) and the F-actin poison cytochalasin B (Fig. 5.3e).…”
Section: Generalcellmorphology(lightmicroscopy)mentioning
confidence: 83%
“…They reported an LC 50 for methoxyfenozide of 0.22 mg/kg, 10 times more toxic to mosquito larvae than RH-5849, tebufenozide, or halofenozide. In more physiological than toxicological reports, both Smagghe et al (2003) and Palli et al (2005) suggested ecdysone agonists could have promise as mosquitocides. Palli et al (2005) reported an EC 50 of 0.67 and 0.45 ppm (length of observation time was not Þxed) for methoxyfenozide (RH-2485) and (1-aroyl-4-(arylamino)-1,2,3,4-tetrahydro-quinoline against Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these observations, it can also be speculated that the cellular long filamentous cytoplasmic extensions of the Se4 cell line as seen in Figure 2B were due to changes in actin content. It has been proven that the cytoplasmatic actin content of responsive cells was doubled during 20E-induced cell elongation (Berger et al, 1981;Couderc et al, 1982;Smagghe et al, 2003a). The commitment to mitotic arrest was very rapid and this mitotic arrest was accompanied by changes in cell shape.…”
Section: Discussionmentioning
confidence: 99%